2022
DOI: 10.1007/s43630-021-00157-0
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inactivation of plant pathogens part II: fungi

Abstract: The constantly increasing demand for agricultural produce from organic and conventional farming calls for new, sustainable, and biocompatible solutions for crop protection. The overuse of fungicides leading to contamination of both produce and environment and the emergence of plant pathogenic fungi that are resistant to conventional treatments warrant the need for new methods to combat fungal infections in the field. We here deliver the follow-up study to our research on the Photodynamic Inactivation (PDI) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Thus, although the photosensitization of fungal structures requires higher PS concentrations, the cellular targets of photosensitization with PS 1 may be sufficiently diverse to support the prospect of a broad-spectrum (multiorganism) phytosanitary approach applicable to plant nurseries. The effectiveness of the two PSs against pathogenic fungal microbes in vitro showed their promising application in an in vivo approach, such as the one presented by Plaetzer and coworkers, who used strawberry leaves and solar light as a green irradiation source [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although the photosensitization of fungal structures requires higher PS concentrations, the cellular targets of photosensitization with PS 1 may be sufficiently diverse to support the prospect of a broad-spectrum (multiorganism) phytosanitary approach applicable to plant nurseries. The effectiveness of the two PSs against pathogenic fungal microbes in vitro showed their promising application in an in vivo approach, such as the one presented by Plaetzer and coworkers, who used strawberry leaves and solar light as a green irradiation source [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Photosensitizers have been observed as effective against bacteria [ 18 ], fungi [ 19 ] and insects such as mosquitoes, ticks and Thrips tabaci Lindeman [ 31 , 32 ]. Glueck et al [ 18 ] reported that the sodium salt of chlorophyllin (Chl, E140), the active ingredient present in SUN-D-06 PS in this study, is effective in controlling the Gram-positive bacterial plant pathogen Rhodocccus fascians and Gram-negative Xanthomonas axonopodis and Erwinia amylovora .…”
Section: Discussionmentioning
confidence: 99%
“…Due to their unique mode of action, photosensitizers could also play an important role in IPM as reduced risk pesticides. Recently, Photodynamic Inactivation (PDI) has emerged as a powerful tool to control both Gram-negative and Gram-positive bacteria, as well as fungi [ 18 , 19 ]. PDI is characterized by the use of a photosensitizer (PS), that when activated by a light source in the presence of molecular oxygen produces reactive oxygen species (ROS) and singlet oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations